Povedenie tsentral'noi gemodinamiki i sokratitel'noi funktsii miokarda v zavisimosti ot napravlennosti trenirovochnogo protsessa v aikido - Eliseev, E. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The echocardiac research of the qualified aikido athletes, divided on three groups on an orientation of training process, dissects the specificity of influence of a mode and a contents of physical loads on parameters central hemodynamics and contractile ability of a myocardium.